SELF CARE SERVICES TO IMPROVE THE MENTAL HEALTH OF BK TEACHERS - Aura, Alma (Jurnal Kopendik, 2023)
These impacts can affect the delivery of professional services to clients and lead to an imbalance between personal and professional life. Many efforts can be made in order to overcome the impact of low psychological well-being of a professional helper. When teachers have good mental health, they can have good emotion regulation, which will have an impact on their efforts in assisting students. Exhaustion and psychological pressure related to stress and felt from day to day, so that it feels a situation that involves high emotionality, and has an impact on a person's physical, emotional and mental exhaustion is referred to as burnout. Self-care is the act of taking care of oneself physically, emotionally, and mentally. In other words, self-care is defined as a self-awareness so that individuals keep growing and developing in a positive way so as to achieve happiness.